Hyponatremia Is Associated With Post-thrombolysis Hemorrhagic Transformation and Poor Clinical Outcome in Ischemic Stroke Patients - He, Ling; Guo, Zhen-Ni; Qu, Yang; Jin, Hang (Frontiers in Molecular Neuroscience, 2022)
Objective: Hyponatremia is the most common electrolyte disorder encountered in patients with neurological conditions such as stroke. Studies have shown that it is associated with worse clinical outcome and increased mortality in acute ischemic stroke (AIS). However, the role of hyponatremia has not been elucidated in patients with AIS who received intravenous thrombolysis therapy. Therefore, this study aimed to investigate the effect of serum sodium levels on clinical outcome and hemorrhagic transformation (HT) in patients with AIS who received thrombolytic therapy. Methods: Patients diagnosed with AIS who received intravenous thrombolysis therapy between May 2015 and December 2020 were included in this study. All patients were screened for serum sodium levels immediately after hospital admission, before intravenous thrombolysis therapy. The occurrence of HT was evaluated using computed tomography 24±2 h after thrombolysis. Three-month clinical outcomes were obtained by telephone calls or outpatient visits, and poor three-month clinical outcomes were defined as modified Rankin Scale scores ≥ 3. The effects of serum sodium levels on clinical outcome and HT were assessed using multivariate logistic regression analysis Results: Of the 963 included patients, 82 (8.5%) had hyponatremia, 157 (16.3%) developed HT, and 333 (34.6%) had poor three-month outcomes. Of the 82 patients with hyponatremia, 21 (25.6%) developed HT, and 39 (47.6%) had poor three-month outcomes. Patients with hyponatremia had a higher incidence of post-thrombolysis HT (25.6% vs. 15.4%, p = 0.017) and worse clinical outcome (47.6% vs. 33.4%, p = 0.01) than those with normal serum sodium levels. Patients with HT had significantly lower serum sodium levels [138.4 (136.4-140.3, IQR) vs. 139.0 (137.2-140.7, IQR) mmol/L, p=0.019] and poor three-month outcomes [139.0 (137.2-140.7) vs. 138.4 (136.7-140.3) mmol/L, p=0.005] than those without HT. After adjusting for major covariates, multivariate logistic regression analysis revealed that lower serum sodium levels were independently associated with an increased risk of HT (OR =1.804; 95% CI: 1.048–3.105) and poor three-month outcome (OR =1.647; 95% CI: 1.012–2.679). Conclusion: Lower serum sodium level was an independent risk factor for post-thrombolysis HT and poor clinical outcome in patients with AIS who received thrombolytic therapy.